2022
DOI: 10.53703/001c.35342
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of External Stakeholders’ Pressures on the Intention to Adopt Environmental Management Practices and the Moderating Effects of Firm Size

Abstract: SMEs in the food manufacturing sector represent a considerable proportion of mainstream businesses in Malaysia. The changes in the lifestyles of Malaysians have led to increased demand for convenience and processed foods, which has led to a growing number of food manufacturing establishments in Malaysia. Nevertheless, the expansion in the food manufacturing sector is followed by a rise in environmental issues. Therefore, to mitigate the impact of food manufacturing activities on the environment, one of the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 115 publications
0
1
0
Order By: Relevance
“…Of the three factors used in this study, the most influential variable on firm intention was found to be subjective norms (f²=0.13). This is consistent with studies conducted by Oduro, Bruno and Maccario (2021) and Latip, Sharkawi, Mohamed and Kasron (2022) who found the presence of a number of high-profile pressure group enhance firms' intention in the adoption of CSR activities.…”
Section: Discussionsupporting
confidence: 91%
“…Of the three factors used in this study, the most influential variable on firm intention was found to be subjective norms (f²=0.13). This is consistent with studies conducted by Oduro, Bruno and Maccario (2021) and Latip, Sharkawi, Mohamed and Kasron (2022) who found the presence of a number of high-profile pressure group enhance firms' intention in the adoption of CSR activities.…”
Section: Discussionsupporting
confidence: 91%
“…This justifies fusing the two theories to explain their hypothesized connection. According to earlier studies (Latip et al, 2022;Panigrahi & Rao, 2018;Pollice, 2010), stakeholders are pressuring firms worldwide to embrace sustainable practices. The focus on sustainability performance has necessitated stronger governance components to hold managers accountable for their actions and reduce agency conflicts, resulting in the integration of both theories (Naciti et al, 2021).…”
Section: Sustainability Performance Of Firms and Governancementioning
confidence: 99%
“…sosial perusahaan merupakan kemampuan perusahaan dalam membangun hubungan baik dengan pihak internal perusahaan (perusahaan dengan karyawan) dan juga pihak eksternal perusahaan (mitra perusahaan, konsumen, kreditur, dan juga masyarakat umum) (Latip et al, 2022dan Singh & Misra, 2021. Maka dalam hal ini Social capital juga berhubungan erat dengan reputasi dan kepercayaan yang dimiliki oleh perusahaan.…”
Section: Modalunclassified